2001
DOI: 10.1006/exer.2001.1060
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin Sulphate Proteoglycan is Involved in Lens Vesicle Morphogenesis in Chick Embryos

Abstract: Proteoglycans have been implicated in the invagination and formation of various embryonal cavitied primordia. In this paper the expression of chondroitin sulphate proteoglycan is analysed (CSPG) in the lens primordium during lens vesicle formation, and demonstrate that this proteoglycan has a speci®c distribution pattern with regard to invagination and fusion processes in the transformation of placode into lens vesicle. More speci®cally, CSPG was detached in: (1) the apical surface of lens epithelial cells, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 55 publications
0
17
0
2
Order By: Relevance
“…They confirm the presence of such a matrix whilst at the same time supporting the idea of dynamic behaviour in the secretion process, related with that of neural fold fusion. Several studies have shown that similar extracellular matrices exist, covering the apical surface of epithelial cells in various embryonal primordia at moments prior to epithelial fusion, for example, in the nasal folds [Gaare and Langman, 1977;Burk et al, 1979], the otic vesicle [Sinning and Olson, 1988], the lens vesicle [Gato et al, 2001] and the palate [Greene and Kochhar, 1974;Pratt and Hassell, 1975;Souchon, 1975]. In this regard, it has been shown that these neuroepithelial cells on the tip of the neural folds or other primordia have ultra-structural characteristics compatible with active secretion processes occurring before fusion [González Santander and Martínez Cuadrado, 1976;Mak, 1978;Rovasio and Monis, 1981;Sinning and Olson, 1988;Alonso et al, 1998a].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They confirm the presence of such a matrix whilst at the same time supporting the idea of dynamic behaviour in the secretion process, related with that of neural fold fusion. Several studies have shown that similar extracellular matrices exist, covering the apical surface of epithelial cells in various embryonal primordia at moments prior to epithelial fusion, for example, in the nasal folds [Gaare and Langman, 1977;Burk et al, 1979], the otic vesicle [Sinning and Olson, 1988], the lens vesicle [Gato et al, 2001] and the palate [Greene and Kochhar, 1974;Pratt and Hassell, 1975;Souchon, 1975]. In this regard, it has been shown that these neuroepithelial cells on the tip of the neural folds or other primordia have ultra-structural characteristics compatible with active secretion processes occurring before fusion [González Santander and Martínez Cuadrado, 1976;Mak, 1978;Rovasio and Monis, 1981;Sinning and Olson, 1988;Alonso et al, 1998a].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no studies to identify specific molecules involved in the neural fold fusion process. On the other hand, we have previously demonstrated the involvement in palatal fusion [Gato et al, 2002] and the crystalline vesicle [Gato et al, 2001] of a CSPG-rich extracellular matrix coating the epithelial apical surface.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 20 embryos were incubated up to stage 17 H.H. (corresponding to that of the lens vesicle, prior to differentiation of lens fibres), at which a single dose of 24 μl β-D-xyloside (a sulphated proteoglycans synthesis disruptor) 4 mM (Sigma) was injected subgerminally with a Hamilton microsyringe [12], and the eggs were reincubated for 24 hours until stage 23 H.H. (corresponding to the development of lens fibres).…”
Section: Obtaining Chick Embryos and Experimental Approachmentioning
confidence: 99%
“…The other mechanism proposed is that of regulation of FGF-2 bioavailability and receptor activation by the extracellular matrix proteoglycans, as described for Heparan Sulphate proteoglycans in many biological systems [9] [10]. In this context, there are previous reports of the presence and involvement of proteoglycans in several aspects of early lens development [11] [12]; in addition, special attention has been given to the influence of the CSPG and HSPG of the lens capsule in lens fibre differentiation in birds and mammals [13] [14], suggesting that HSPG from the lens capsule might be involved in lens fibre differentiation by FGF-2 activity regulation [15]. However, experimental support for this relation is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Camundongos com afaquia congênita (animais com ausência de cristalino) apresentam alterações na composição desta matriz extracelular (Zwaan e Webster, 1984). Além disso, a injeção de inibidores da síntese de glicosaminoglicanas, ou de enzimas que degradam proteoglicanas, no espaço entre a vesícula e o placóide, interferem na invaginação do cristalino (Gato et al, 2001). …”
Section: O Movimento Inteunclassified